The Impact of ESCRT on Aβ1-42 Induced Membrane Lesions in a Yeast Model for Alzheimer’s Disease - Fruhmann, Gernot; Marchal, Christelle; Vignaud, Hélène; Verduyckt, Mathias; Talarek, Nicolas; De Virgilio, Claudio; Winderickx, Joris; Cullin, Christophe (Frontiers in Molecular Neuroscience, 2018)
Aß metabolism plays a pivotal role in Alzheimer’s disease. Here, we used a yeast model to monitor Aß42 toxicity when entering the secretory pathway and demonstrate that processing in, and exit from the endoplasmic reticulum (ER) is required to unleash the full Aß42 toxic potential. Consistent with previously reported data, our data suggests that Aß42 interacts with mitochondria, thereby enhancing formation of reactive oxygen species and eventually leading to cell demise. We used our model to search for genes that modulate this deleterious effect, either by reducing or enhancing Aß42 toxicity, based on screening of the yeast knockout collection. This revealed a reduced Aβ42 toxicity not only in strains hampered in ER-Golgi traffic and mitochondrial functioning but also in strains lacking genes connected to the cell cycle and the DNA replication stress response. On the other hand, increased Aβ42 toxicity was observed in strains affected in the actin cytoskeleton organization, endocytosis and the formation of multivesicular bodies, including key factors of the ESCRT machinery. Since the latter was shown to be required for the repair of membrane lesions in mammalian systems, we studied this aspect in more detail in our yeast model. Our data demonstrated that Aβ42 heavily disturbed the plasma membrane integrity in a strain lacking the ESCRT-III accessory factor Bro1, a phenotype that came along with a severe growth defects and enhanced loading of lipid droplets. Thus, it appears that also in yeast ESCRT is required for membrane repair, thereby counteracting one of the deleterious effects induced by the expression of Aß42. Combined, our studies once more validated the use of yeast as a model to investigate fundamental mechanisms underlying the etiology of neurodegenerative disorders.